Responding to shock: a collaborative process for the St. Roch neighborhood - Mahoney, J. Liam (Kansas State University, 2011)
Hurricane Katrina displaced many New Orleans residents, leaving in its wake tens of thousands of vacant lots and buildings. In 2010, estimates show that over 57,000 properties lay empty in the city, especially in the poorer neighborhoods. These properties are not contributing to the fabric of the city; in most places, they are a sign of defeat, an eyesore, or a haven for crime. The neighborhood of St. Roch is experiencing the negative effects of these properties day in and day out and from year to year. Almost a quarter of the lots are vacant in the St. Roch neighborhood, leading to crime and creating a nuisance and a blemish on the community. Coupled with the lack of ownership there is an ailing stormwater management infrastructure leading to areas of flooding after routine storms. In addition to these concerns, there is a lack of fresh, inexpensive and accessible food throughout the area. Although St. Roch’s vacant lots have a negative effect on the community, they present a tremendous opportunity. Their dispersal around the neighborhood presents the opportunity to connect them to churches, schools, retail outlets, as well as providing other uses and services to the neighborhood. The thoughtful design of these locations will demonstrate a site-sensitive approach to the local ecology, culture, and economy of the neighborhood. Such design includes the community throughout the entire lifecycle of each site from its planning phase to the end of its use. The primary goal throughout the planning and design process is to foster stewardship for both the landscape and the community as a whole by means of collaborative planning, direct interaction with each site during implementation, and the observation and monitoring of crucial processes throughout a site’s lifecycle. The intent of this project is to apply a participatory framework to the site design process in order to rejuvenate critical areas of the St. Roch neighborhood. This project seeks to demonstrate the need for a collaborative process while allowing for a balance between the experts who help design each site and the community members who take ownership of the renewed parcels.
Keywords: Stormwater management; New Orleans; St. Roch Neighborhood; Wetlands design; Collaborative planning; Urban agriculture; Landscape Architecture (0390); Urban Planning (0999)